HUMANITAS YURISPRUDENSI AYAT WARIS: Membaca Konsep Alquran Mengenai Warisan ‘ala Ahmad an-Na’im - Wathani, Syamsul (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2019)
This article focuses on reinterpreting inherited verses using Ahmad an-Na'im's reading pattern. Interpretative-explorative analysis. This analysis produces several conclusions: (a) Reading for reality is an alternative view to revive the Qur'an so that it has a paradigm in looking at reality. (b). In the analysis of the inheritance verse (Surah An-Nisa 'verse 11), reading of reality, the acceptance of the inheritance doubled from the portion received by women, shows the superiority of men over women, because of some illat. Whereas in the reading for reality analysis, the Al-Qur'an presents new regulations on inheritance. This regulation can be used in giving birth to the Qur'an fiqh concerning inheritance in the present context.